PENGARUH MANTRAM GAYATRI TERHADAP TINGKAT DEPRESI PADA PASIEN HEMODIALISA DI RUMAH SAKIT X DI DENPASAR - Ni Made Resiani; Ni Putu Dita Wulandari; Ni Komang Matalia Gandari (Coping: Community of Publishing in Nursing, 2021)
The number of CKD sufferers who underwent hemodialysis in 2019 was 15,6 milion people who experienced depression, 8% of whom sought treatment from professionals. In Bali there are 200.000 patients undergoing hemodialysis and only 430 patients per month. Psychological impact include complaining of muscle weakness, feeling tired, emotional instability, spiritual psychological pressure (depression). Financial burdens and lack of social support. This study aims to determine the effect of the gayatri mantram on the level of depression in hemodialysis patients at hospital X in Denpasar. The study is quantitative type, the method is pre-experimental with one group pre-test post-test design approach. Data analysis using the Liliefort test. The results obtained after being given Gayatri mantram therapy with z value of -5.375 and p value = 0.001 therefore it can be concluded that there was an effect of gayatri mantram therapy on depression level depression in hemodialysis patient at Hospital X in Denpasar. Suggestions: need to be applied about the importance of gayatri mantram therapy especially for hemodialisys patients to reduce the depression levels. Key words: hemodialysis, depression, gayatri mantram